The application of research in organisational communication - Gustav Puth (Communicare)
As with most other forms of communication, the most pressing problems of organisational communication can be localised within the limits of the two basic human communication prerequisites of anticipation and feedback: establishing the identity and nature of your receiver(s) as a basis for message formulation, and establishing the receiver reaction (in its broadest sense) on the message as a basis for continued communication. This paper proposes a number of basic research applications as possible solutions to these problems.